Evaluation of methods of modeling and formation of experimental allergic encephalomyelitis - Nefodov, O. O.; Belenichev, I. F.; Fedchenko, M. P.; Popazova, O. O.; Ryzhenko, V. P.; Morozova, O. V.; Бєленічев, Ігор Федорович; Попазова, Олена Олександрівна; Риженко, Віктор Павлович; Морозова, Оксана Валентинівна (My University, 2022)
Introduction: Experimental autoimmune (allergic) encephalomyelitis (EAE) induced by intradermal injection of homogenate of the brain, spinal cord and peripheral nerve with Freund’s stimulator, refers to a true autoimmune disease of the nervous system. Materials and methods: Experimental studies were conducted on white nonlinear rats. To induce experimental allergic encephalomyelitis (EAE), homologous brain homogenates was used, which leads among other drugs (homologous, heterogeneous brain and spinal cord homogenates) by encephalitogenity. The connective tissue of the animal’s tail base was injected with a mixture of encephalitogenic suspension of 0.1 ml per 100 g of the body weight. Results and discussion: According to the results, in the rats, there was weight loss, and the abnormal neurological symptoms were found on an average of 10–12th days. Our experimental studies on the formation of EAE were confirmed morphologically by electron microscopy. Conclusion: Thus, the use of this technique allowed us to obtain a simulated pathologic condition of multiple sclerosis in the form of experimental allergic encephalomyelitis and can be used in future studies to identify appropriate laws, the extent and nature of changes in the immune and nervous systems of the body when inducing experimental pathological conditions.
I. F. Belenichev - https://orcid.org/0000-0003-1273-5314; O. O. Popazova - https://orcid.org/0000-0001-7740-460X; V. P. Ryzhenko - https://orcid.org/0000-0003-3466-7148; O. V. Morozova - https://orcid.org/0000-0003-0763-1369.
Keywords: multiple sclerosis; experimental allergic encephalomyelitis; experimental model of demyelinating state